KORELASI SEDENTARY LIFESTYLE, DURASI TIDUR DAN ASUPAN GIZI DENGAN STATUS GIZI REMAJA (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2020)
Adolescents often experience nutritional problems related to the development and growth of adolescent bodies that require energy and nutrients. The problems experienced by adolescents are not only diet but also on sedentary lifestyles. This study aimed to determine the correlation between sedentary lifestyle, sleep duration, fiber, and fat intake with nutritional status in adolescent girls. This study uses a cross-sectional observational analytic design conducted at two high schools in Buleleng Regency with 163 respondents. The instruments used in this study were characteristic questionnaire, Adolescent Sedentary Activities Questionnaire (ASAQ), Quality Time application to measure the duration of smartphone usage, sleep duration questionnaire, 2x24 hour food recall, bodyweight measure with a body weight scale, body height measure with a mechanical measuring tape, and WHO AnthroPlus software to calculate z-score. Spearman’s Correlation test was performed for the bivariate analysis and multiple linear regression for the multivariate analysis. Bivariate analysis showed 3 variables including sleep duration (p = 0,001), fat intake (p = <0,001) and sedentary lifestyle (p = 0,027) associated were with z-score. In the multivariate analysis, only 2 variables were significantly associated with z-score, the percentage of fat intake (? = 0,348, 95% CI = 0,014: 0,033, p=<0,001), and sleep duration variable (? = -0,206, 95% CI = -0,504: -0,086, p=0,006). Variables that are predictors of z-score were the percentage of fat intake, sleep duration, sedentary lifestyle, percentage of fiber intake, frequency of exercise per week, and family income.